(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The exponential growth of social media platforms has significantly reshaped patterns of communication, interaction, and identity formation among students in higher education. While these digital platforms facilitate knowledge sharing, networking, and social engagement, their pervasive use has raised serious concerns regarding students’ mental health. This research paper critically examines the impact of social media on student mental well-being through an integrated legal and ethical framework.Adopting a doctrinal and analytical methodology, the study evaluates existing legal provisions governing digital environments, including mental health legislation and information technology laws, alongside ethical principles such as autonomy, privacy, beneficence, and non-maleficence. The analysis highlights that although legal mechanisms provide a foundational structure for regulating cyber activities, they remain insufficient in addressing emerging forms of psychological harm caused by prolonged exposure to algorithm-driven content, cyberbullying, and digital dependency. The paper further explores ethical challenges associated with data surveillance, behavioural manipulation, and lack of transparency in platform algorithms, which often exploit users’ cognitive vulnerabilities. Particular emphasis is placed on the responsibility of social media companies and educational institutions in creating a safe and supportive digital ecosystem for students.The findings reveal a significant gap between technological advancements and regulatory safeguards, compounded by inconsistent institutional policies and limited awareness among students. In response, the paper proposes a multi-dimensional approach involving legal reforms, stricter platform accountability, enhanced institutional interventions, and the promotion of digital literacy and mental health advocacy. In conclusion, the study underscores that safeguarding student mental health in the digital age requires a coordinated effort that integrates legal regulation, ethical governance, and proactive institutional responsibility, thereby ensuring a balanced and healthy engagement with social media.